Natural Resources, Institutions, and Economic Growth : The Case of Nigeria - Raggl, Anna K. (World Bank, Washington, DC, 2017)
Using growth regressions with panel data, this study identifies the determinants of economic growth, highlighting in particular the role of natural resources and institutional quality. The overarching aim of this exercise is to learn about the drivers of growth in Nigeria, and to predict growth rates of gross domestic product per capita for the country under different scenarios. This study finds that a growth-enhancing effect of natural resources is tied to a sound institutional environment and low levels of corruption. Accumulation of human as well as physical capital, but also the quality of institutions and natural resource rents are estimated to be particular important ingredients for a prosperous economic development in Nigeria.